Financing diversification and Indonesian Islamic bank's non-performing financing - Agus Widarjono; Ari Rudatin (Faculty of Economics, Universitas Islam Indonesia, 2021)
Purpose – This study empirically analyzes the effect of the financing diversification with some control variables including both bank-specific variables such as bank's size, CAR, efficiency and the macroeconomic variables such as the inflation and exchange rate, on the Islamic bank's non-performing financing (NPF).Methodology – The aggregate Islamic bank data encompassing Islamic commercial banks and Islamic business units are used. The Autoregressive Distributed Lag Model (ARDL) is employed using the monthly data covering January 2011 to December 2019.Findings – The cointegration test indicates that the long-run relationship among variables being studied exists. Our results document that higher concentrated financing generates high NPF. Higher asset significantly contributes to reducing NPF. In addition, higher operating efficiency can reduce NPF. The instability of the exchange rate also generates the high NPF.Research limitations – This study employs aggregate data but applying them may conceal for individual Islamic bank.Practical implications – Our results suggest that Islamic banks must lessen the high concentrated financing by optimizing both PLS and non-PLS contracts to reduce Islamic banks' financing risk.Originality – Our study includes financing diversification to examine Islamic bank's financing risk. The existing empirical studies, to the best of our knowledge, have not addressed the impact of financing diversification on financing risk.